The effect of deposition parameters on the properties of CeCl3 and LaCl3 conversion coatings deposited on three Al-based substrates - Volarič, Barbara; Mazare, Anca Valentina; Virtanen, Sannakaisa; Milošev, Ingrid (Corrosion, 2020)
Cerium and lanthanum conversion coatings were deposited from solution of CeCl3 and LaCl3 salts on three aluminum-based substrates: Al, AA2024-T3, and AA7075-T6 to investigate the effect of conversion temperature, conversion time, and addition of hydrogen peroxide. Coatings prepared under different conditions were then analyzed in terms of corrosion properties in 0.1 M NaCl, morphology, topography, and composition. Morphology and composition of the coatings were analyzed using scanning electron microscopy with energy dispersive x-ray spectrometry and x-ray photoelectron spectroscopy. Corrosion resistance, morphology, composition, and homogeneity of coatings were largely dependent on parameters of conversion treatment and type of substrates. Most corrosion resistants were Ce-based coatings produced at 60°C for 1 h in a bath containing CeCl3 and H2O2. La-based coating did not reach comparative resistance when deposited under the same conditions. Morphology of coatings ranged between individual deposits to thick, cracked coatings with nodular morphology. Ce-based coatings predominantly contained Ce(IV) hydroxide when formed with added H2O2. La-based coatings contained La(III) hydroxide mixed with Al(III) hydroxide.
CRIS-Team Scopus Importer:2020-01-28
Keywords: Aluminum alloys; Cerium; Conversion coatings; Corrosion; Lanthanum; Rare earth chloride